Stretchable freezing-tolerant triboelectric nanogenerator and strain sensor based on transparent, long-term stable, and highly conductive gelatin-based organohydrogel. (May 2022) - Wu, Min; Wang, Xin; Xia, Yifan; Zhu, Yan; Zhu, Shunli; Jia, Chunyang; Guo, Wenyu; Li, Qingqing; Yan, Zhengguang
Abstract: Conductive hydrogels have attracted tremendous attention for the next-generation electronic/energy/robotic application owing to their excellent mechanical and electrical properties, including stretchability, high conductivity, and stability. How to simultaneously realize their highly transparent, self-healing, antifreezing/antidrying, biocompatible and highly conductive features through a simple approach is still a challenge. Herein, the stretchable freezing-tolerant triboelectric nanogenerator (TENG) and strain sensor have been developed based on a transparent, long-term stable, and highly conductive gelatin/NaCl organohydrogel (GNOH), which is prepared via a facile immersion strategy in a glycerol/water binary solvent. The GNOH demonstrates superior merits of strain (300%), transparency (85%), high conductivity (1.6 S/m), freezing tolerance (−20 ℃), self-healing capability (91%), and environment stability (over 30 days). Furthermore, the wearable strain sensors enable the detecting, quantifying, and monitoring of human activities with high sensitivity of about 2.5 (strain of 0–200%). Meanwhile, the fabricated TENG in single-electrode mode can achieve excellent electrical outputs to power portable electronics when efficiently harvesting biomechanical energies, even at harsh cold temperature (−20 ℃). Additionally, a flexible self-powered calculator based on the arrayed TENG as touch panel is also explored for human-machine interaction (HMI). This study paves the way for potential applications in wearable electronics, healthcare monitoring, biomechanical energy harvesting and HMI. Graphical Abstract: ga1 Stretchable freezing-tolerant triboelectric nanogenerator (TENG) and strain sensor has been proposed based on transparent, long-term stable, and highly conductive gelatin/NaCl-based organohydrogel (GNOH). The GNOH demonstrates excellent characteristics of mechanical stretchability, freezing tolerance, long-term ambient stability, and self-healing capability. The fabricated TENG and wearable strain sensor enable the real-time monitoring of human motion and harvesting of biomechanical energy. Highlights: Organohydrogel demonstrates superior merits of strain (300%), transparency (85%), high conductivity, and freezing tolerance. The wearable strain sensors enable the detecting, quantifying, and monitoring of human activities. The fabricated AG-TENG at −20 ℃ can achieve excellent electrical outputs when harvesting biomechanical energy. A flexible self-powered calculator based on the arrayed TENG as touch panel is also explored for human-machine interaction.